2018
DOI: 10.30573/ks--2018-dp47
|View full text |Cite
|
Sign up to set email alerts
|

The Policymaking Process to Restart Japanese Nuclear Power Plants

Abstract: The King Abdullah Petroleum Studies and Research Center (KAPSARC) is a non-profit global institution dedicated to independent research into energy economics, policy, technology and the environment across all types of energy. KAPSARC's mandate is to advance the understanding of energy challenges and opportunities facing the world today and tomorrow, through unbiased, independent, and high-caliber research for the benefit of society. KAPSARC is located in Riyadh, Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The initial paper presented plausible conclusions for the CDMP on Japanese nuclear reactors (Efird et al 2018). It showed that it is politically feasible to restart many more nuclear reactors in Japan.…”
Section: Ktab and The Spatial Model Of Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial paper presented plausible conclusions for the CDMP on Japanese nuclear reactors (Efird et al 2018). It showed that it is politically feasible to restart many more nuclear reactors in Japan.…”
Section: Ktab and The Spatial Model Of Politicsmentioning
confidence: 99%
“…A s mentioned earlier, this paper is part of a series of three papers that draw on KTAB simulation analyses to assess the political feasibility of restarting each Japanese nuclear reactor, which would help determine the rate of reintegration of nuclear energy into the power mix. A more complete description of the modeling process used can be found in Efird et al (2018).…”
Section: Ktab and The Spatial Model Of Politicsmentioning
confidence: 99%
“…Local politics can also directly influence global energy markets. Following the Fukushima incident, certain local players, such as the mayors of Mihama and Takahama and power companies such as the Kansai Electric Power Company (KEPCO) and Yonden, played important roles in shaping the national debate on whether to restart Japan's nuclear plants (Efird et al 2018). The national government's eventual decision, in turn, will have important repercussions for global energy markets.…”
Section: The Local Levelmentioning
confidence: 99%
“…KTAB simulates collective decision-making processes (CDMPs) among a set of players (characteristically between five and 50) over a number of turns of negotiation, based on data obtained from semi-structured interviews with subject matter experts. Studies employing KTAB have analyzed topics including country-level compliance with announced nationally determined contributions (Al Quayid et al [forthcoming]), Japan's decision to restart nuclear investments after the Fukushima accident (Efird et al 2018), and the political feasibility of a Gulf Cooperation Council (GCC)-wide power market (Mollet et al 2018).…”
Section: Modeling Collective Decision-making Processes: Ktab and Compmentioning
confidence: 99%
“…This paper is the second of three looking into the political will in Japan to restart the country's nuclear reactors. The first, "The Policymaking Process to Restart Japanese Nuclear Power Plants" (Efird et al 2018) evaluated the political feasibility of restarting Japan's nuclear reactors amid a continuously changing political climate in the aftermath of the Fukushima-Daichii accident. The KTAB data inputs used for that study meant that it was one of the more complex questions to be analyzed, and led to very interesting results.…”
Section: Introductionmentioning
confidence: 99%